2019
DOI: 10.1002/gepi.22187
|View full text |Cite
|
Sign up to set email alerts
|

A large‐scale exome array analysis of venous thromboembolism

Abstract: Although recent Genome‐Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome‐wide search for low‐frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta‐analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…The development of several so-called next generation sequencing (NGS) or High-Throughput Nucleotide Sequencing platforms is offering the possibility of generating fast, inexpensive and accurate genomic information, reviewed by Cunha et al [54]. A few such studies have been published [55][56][57][58][59][60][61][62][63][64]. These studies could be either agnostic [61][62][63][64], i.e.…”
Section: High-throughput Nucleotide Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of several so-called next generation sequencing (NGS) or High-Throughput Nucleotide Sequencing platforms is offering the possibility of generating fast, inexpensive and accurate genomic information, reviewed by Cunha et al [54]. A few such studies have been published [55][56][57][58][59][60][61][62][63][64]. These studies could be either agnostic [61][62][63][64], i.e.…”
Section: High-throughput Nucleotide Sequencingmentioning
confidence: 99%
“…A few such studies have been published [55][56][57][58][59][60][61][62][63][64]. These studies could be either agnostic [61][62][63][64], i.e. whole exome sequencing (WES) or whole genome sequencing (WGS), or using NGS for resequencing of targeted candidate genes [55][56][57][58][59][60].…”
Section: High-throughput Nucleotide Sequencingmentioning
confidence: 99%
“…Multiple subsequent studies have revealed associations with a range of diseases, with a prominent example being a decreased risk of thromboembolic events and increased risks of some hemorrhagic events in individuals with blood group O ( Franchini et al, 2012 ; Edgren et al, 2010 ; Vasan et al, 2016a ). The difference in thrombotic and hemorrhagic phenotypes has been attributed to variability in levels of Factor VIII and von Willebrand factor , where ABO status may explain as much as 30% of this variability ( Franchini et al, 2012 ; Orstavik et al, 1985 ; Germain et al, 2015 ; Lindström et al, 2019 ; O'Donnell et al, 2002 ) Other prominent examples include associations with risks of a number of infectious diseases, to the extent that the allele distribution of the blood group antigens has evolved to reflect some areas endemic to these infectious diseases ( Franchini and Bonfanti, 2015 ). This is in part true for infectious disease such as Plasmodium falciparum malaria, Helicobacter pylori , and Vibrio cholera , where ABO blood groups are involved in different aspects of pathogenesis, from microbe attachment and entry into cells to subsequent disease development and severity of disease ( Stowell and Stowell, 2019a ; Franchini and Bonfanti, 2015 ; Cserti and Dzik, 2007 ; Degarege et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a metanalysis of large-scale exome array analyses of VTE failed to identify novel VTE genes. 63…”
Section: Large-scale Genomic Screening Studiesmentioning
confidence: 99%